2022
DOI: 10.1111/jfpp.16339
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of antimicrobial and antioxidant activities of selected plant‐based mayonnaise‐derived essential oils against lactic acid bacteria

Abstract: The development of new technologies such as artificial intelligence (AI), wet extrusion, and mimicking has led to a significant evolution of the food industry, consumer perceptions, and environmental protection policies. These drivers have influenced the plant-based market, leading to a significant increase in the production of plant-based products in the last five years (Aschemann-Witzel et al., 2020). Some of these products include plant-based burgers (De Marchi et al., 2021), sausages (Estell et al., 2021),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Compared with other active components of plant essential oil, cinnamaldehyde has the strongest inhibitory activity on the synthesis of aflatoxin and ochratoxin. The minimal inhibitory concentration of cinnamaldehyde against F. oxysporum and F. gramineum is 0.8 mg/mL, and its minimal inhibitory concentration against spoilage yeast is 0.31-1.25 mg/mL (Muñoz-Gonzaĺez et al, 2022). However, its minimal inhibitory concentration against lactic acid bacteria varies, with a minimal inhibitory concentration of 5 mg/ mL against Lactobacillus sakei and a minimum inhibitory concentration of 50 mg/mL against Lactobacillus brucei (Sameza et al, 2016;Sharma et al, 2017;Muñoz-Gonzaĺez et al, 2022).…”
Section: Main Bacteriostatic and Fungistatic Components And Activitie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other active components of plant essential oil, cinnamaldehyde has the strongest inhibitory activity on the synthesis of aflatoxin and ochratoxin. The minimal inhibitory concentration of cinnamaldehyde against F. oxysporum and F. gramineum is 0.8 mg/mL, and its minimal inhibitory concentration against spoilage yeast is 0.31-1.25 mg/mL (Muñoz-Gonzaĺez et al, 2022). However, its minimal inhibitory concentration against lactic acid bacteria varies, with a minimal inhibitory concentration of 5 mg/ mL against Lactobacillus sakei and a minimum inhibitory concentration of 50 mg/mL against Lactobacillus brucei (Sameza et al, 2016;Sharma et al, 2017;Muñoz-Gonzaĺez et al, 2022).…”
Section: Main Bacteriostatic and Fungistatic Components And Activitie...mentioning
confidence: 99%
“…A number of reports have shown that peppermint essential oil inhibits the cell activity of S. aureus (Kang et al, 2019), Candida albicans, Pseudomonas aeruginosa (Mahboubi and Kazempour, 2014), Helicobacter pylori, and Salmonella enteritidis (Imai et al, 2001). The in vitro antiaflatoxin concentration of menthol is 1.0 mg/mL, while menthol stereoisomers and menthone do not show evident antitoxin function, which is related to their structural types (Ownagh et al, 2010;Muñoz-Gonzaĺez et al, 2022). Peppermint essential oil has weaker bacteriostatic and fungistatic activity than menthol.…”
Section: Main Bacteriostatic and Fungistatic Components And Activitie...mentioning
confidence: 99%
“…Recently, chitosan and its methylated derivatives have been reported to be active as antimicrobials to inhibit Lentilactobacillus parabuchneri biofilms [6]. In another study, an oregano-derived essential oil showed antimicrobial activity against L. parabuchneri [7].…”
Section: Introductionmentioning
confidence: 97%